The role of small heterodimer partner in nonalcoholic fatty liver disease improvement after sleeve gastrectomy in mice. (November 2014) - Myronovych, Andriy; Salazar‐Gonzalez, Rosa‐Maria; Ryan, Karen K.; Miles, Lili; Zhang, Wujuan; Jha, Pinky; Wang, Li; Setchell, Kenneth D. R.; Seeley, Randy J.; Kohli, Rohit
<x xml:space="preserve">Abstract</x> Objective Bile acids (BA) are elevated after vertical sleeve gastrectomy (VSG) and farnesoid‐X‐receptor (FXR) is critical to the success of murine VSG. BA downregulate hepatic lipogenesis by activating the FXR‐small heterodimer partner (SHP) pathway. The role of SHP in fatty liver disease improvement after VSG was tested. Methods Wild type (WT), SHP liver transgenic (SHP‐Tg), and SHP knockout (SHP‐KO) high‐fat diet (HFD) fed mice underwent either VSG or Sham surgery. Body weight, BA level and composition, steatosis, and BA metabolism gene expression were evaluated. Results Obese WT mice post‐VSG lost weight, reduced steatosis, decreased plasma alanine aminotransferase (ALT), had more BA absorptive ileal area, and elevated serum BA. Obese SHP‐Tg mice post‐VSG also lost weight and had decreased steatosis. SHP‐KO mice were however resistant to steatosis despite weight gain on a HFD. Further SHP‐KO mice that underwent VSG lost weight, but developed hepatic inflammation and had increased ALT. Conclusions VSG produces weight loss independent of SHP status. SHP ablation creates a proinflammatory phenotype which is exacerbated after VSG despite weight loss. These inflammatory alterations are possibly related to factors extrinsic to a direct manifestation of NASH.